Typification of intraspecific taxa in Solanum andigenum Juz. et Buk. - N. A. Oskina; T. A. Gavrilenko; I. G. Chukhina (Труды по прикладной ботанике, генетике и селекции)
Taxonomic studies were carried out in the collection of cultivated potato species kept in the Herbarium of Cultivated Plants of the World, Their Wild Relatives, and Weeds (WIR). It allowed us to proceed with typifying the names of intraspecific taxa within Solanum andigenum Juz. et Buk., belonging to three geographical groups: Colombian, South Peruvian, and Bolivian. The WIR herbarium collections comprise the taxonomic diversity of cultivated potatoes described by Russian taxonomists and based on the study of plant materials collected in South America during the expeditions organized by N. I. Vavilov in the late 1920s – early 1930s. Verification of protologs and herbarium specimens resulted in locating herbarium sheets that appeared to be syntypes of six varieties and eleven forms. Lectotypes were also designated for the following three forms: S. andigenum f. huaman-uma Buk. et Lech., S. andigenum f. lecke-umo Buk. et Lech., S. andigenum f. pacus Lech.